Modeling Electricity Consumption for Growth in an Open Economy - Stamatiou, Pavlos (International Journal of Energy Economics and Policy, 2022)
The purpose of this paper is to analyze the long run equilibrium relationship of electricity consumption in Italy from a unique perspective, taking tourism expansion as a proxy for exogenous growth. The sample used is annual data covering the period 1990-2018. The Autoregressive Distributed Lag (ARDL) bounds testing approach and the causality method of Toda and Yamamoto (1995) are applied, as the most appropriate for the integration of the variables and the sample size. The ARDL results, as well as additional cross checking test, reveal a long run relation between electricity consumption, foreign tourist arrivals and economic growth in the country. Foreign tourist arrivals and economic growth have significant impact on electricity consumption, both in the short and in the long run. Τhe causality results support unidirectional causalities running from foreign tourist arrivals and economic growth to electricity consumption. In addition, foreign tourist arrivals influence electricity consumption both directly and indirectly through economic growth. Policy implications are further discussed.